PENGGUNAAN FITOHORMON EKSTRAK BAWANG MERAH (Allium cepa L.) UNTUK PERTUMBUHAN MATERI SETEK BATANG PANGKAL, TENGAH, DAN PUCUK TANAMAN MURBEI (Morus multicaulis) - Nengsih, Nengsih; Muin, Abdurrani; M, Iskandar A (JURNAL HUTAN LESTARI, 2019)
The research aim to determine the effect of the use of phytohormone extracts of red onion (Allium cepa), stem cuttings material and the interaction of phytohormone extracts of A. cepa with stem cuttings material on the growth of mulberry (Morus multicaulis) plants. This research was conducted at the Research and Development Institute of Tanjungpura University from March to May 2019. The method of research was an experimental method with a Split Plot Design. The treatments consisted of the stem cutting materials (base, middle and shoot) as the main plot and the dose of shallots extract (0 g/l, 500 g/l and 1000 g/l) as subplots. Each treatment consisted of three groups, so that the total of treatments were 27 plots. The results showed that only the dose of shallots extract which significant influented on the M. multicaulisÂ  growth. Whereas the stem cutting materials and interactionsof both were did not effect significantly. The highest of murbei growth was obtained at 1000 g/l of shallot extract on 6,52% of the leaves number, 500 g/l of branch length 4,52% and 3.88% of the roots number. Thus, the extract of A. cepa L can be used as an alternative for plant growth, especially M. multultulis plants.Keywords: Mulberry, stem cuttings, phytohormone.